Independent or embedded - Herman Wasserman; Lizma van Zyl (Communicare)
This article explores different viewpoints about the question of journalistic independence in the current South African dispensation by taking the Presidential Press Corps (PPC) as an example. It is argued that when seen from a libertarian point of view, the PPC presents some problems with regard to the normative ethical framework that sees media independence as a position that brings the media and the government in opposition. The views of journalists and editors are canvassed to illustrate some of the concerns about the PPC. The article concludes by suggesting different ways to view the relationship between the government and the media that would not present the same ethical difficulties as when this relationship is viewed from an orthodox libertarian perspective.